Anger in Islam and its Relevance to Mental Health - Muhajara, Kurnia (Jurnal Ilmiah Syi'ar, 2022)
Excessive direction is called ifrath, and not being angry is called tafrith/ shortage. While placing anger at the right time is called i'tidal / balanced. The main problem of this research, how is anger in Islam and its relevance to mental health? This research uses a type of library research (library research) with a descriptive analysis approach. The results showed that feeling annoyed and angry is a human thing to happen. One of the things that are affected when holding anger is a disturbance to one's mental health. Mental health can be disrupted because you always hold on to frustration, hurt, to disappointment. Indeed, anger that arises can be turned into something harmful or beneficial. Anger triggers the body to decide to defend or fight. These emotions trigger responses, such as fear, excitement, to anxiety. The body will be filled with hormones that cause stress, such as adrenaline and cortisol. Frequent temper tantrums will have a negative impact on your heart health. Anger can trigger physiological changes that affect the blood, temporarily increasing the risk of a heart attack or related problems. Thoughts and emotions can affect health. Emotions that are free and can be expressed naturally will not affect health. However, depressed emotions (especially fear or negative feelings) can drain mental energy, negatively impacting the body and causing health problems.